IDENTIFICATION OF Escherichia coli AND Salmonella sp. ON SOME PLANTATION PRODUCTS - Oktora Matondang, Christina; Muklasin, Muklasin; Nurhayati, Nurhayati (CV. Radja Publika, 2023)
Identification of Escherichia coli and Salmonella sp. In Several Plantation Products, the aim is to explain the results of the identification test of E. coli and Salmonella sp. on plantation products. The research was carried out with 4 treatments and 2 replications. Each replication consisted of 5 dilutions. The treatments used were cocoa powder, compost, water and lettuce in selective growing media (EMBA and SSA). The parameters observed were to see whether there were E. coli or Salmonella sp. that grew in the four samples, the number of colonies and color changes that occurred as well as gas or bubbles produced in the fermentation test of sugars (glucose, sucrose and lactose). Based on the test results, it was found that E. coli and Salmonella were not present in the cocoa powder samples in EMBA and SSA media. In the compost sample, the bacteria E. coli grew on EMBA media, but Salmonella bacteria did not grow on SSA media. Lettuce samples showed E. coli growing on EMBA media, while on SSA media there was E. coli and Salmonella bacteria. Meanwhile, in water samples, E. coli, Salmonella and other bacteria grew on EMBA media. And on SSA media, Salmonella and Shigella bacteria grow. In the fermentation test of sugars such as glucose, sucrose and lactose, the media changes color to yellow and there are gas/air bubbles. This shows that bacteria can ferment carbohydrates and can produce gas. Salmonella and other bacteria grow on EMBA media. And on SSA media, Salmonella and Shigella bacteria grow. In the fermentation test of sugars such as glucose, sucrose and lactose, the media changes color to yellow and there is gas/air bubbles. This shows that bacteria can ferment carbohydrates and can produce gas. Salmonella and other bacteria grow on EMBA media. And on SSA media, Salmonella and Shigella bacteria grow. In the fermentation test of sugars such as glucose, sucrose and lactose, the media changes color to yellow and there is gas/air bubbles. This shows that bacteria can ferment carbohydrates and can produce gas.